EFFECT OF SOYBEAN SEED PRIMING ON GERMINATION ENERGY - Miladinov, Zlatica J; Balešević-Tubić, Svetlana; Đukić, Vojin; Veselić, Jelica; Ilić, Aleksandar; Čobanović, Lazar; Merkulov-Popadić, Larisa (Journal of Agricultural Sciences (Belgrade), 2019)
Summary: Six varieties were chosen from three different maturity groups: Galina and NS Princeza (0), Sava and NS Apolo (I), and Rubin and NS Zita (II) in order to examine the effect of immersion on germination energy depending on soybean seed age. The seed was produced in the period from 2012 to 2014, i.e., three, two, and one year old seed was used. The following treatments were used for immersion: distilled water – hydropriming (H2O), ascorbic acid 250 mg/l (ASA), folic acid 15 mg/l (Fol.), hydrogen peroxide 1% (H2O2), and control – non-treated seed (C). Results showed that the effects of priming depended on the variety, seed age, as well as the applied treatment. Some varieties reacted to immersion very well, while others had an inhibited reaction, so germination energy was significantly reduced. Rubin variety had the most favourable reaction, whereby all treatments of this variety led to increase of quality, with an average increase of 2-8%. Application of primers on one-year-old soybean seed had a weaker effect than on two- and three-year-old seed. However, one-year-old seed had minor oscillations in quality due to priming. Application of priming on one-year-old seed can lead to increase or decrease of germination energy by 3%, while two- and three-year-old seed reached 7%. The results showed that seed immersion in ascorbic acid had a positive effect, while the application of other primers did not affect the value of germination energy, or led to decrease of its value. Ascorbic acid activity led to the largest increase in the quality of three-year-old soybean seed by 2.83%, while the increase in the quality of two- and three-year-old seed was 1.87%. Therefore, we can conclude that there is no universal use of one single primer, as it might not be suitable for each particular cultivar and can ultimately result in seed quality decrease. Key words: germination energy, priming, aging seed, soybean